Granular Geomechanics. - Kuhn, Matthew R. (Elsevier Science, 2017)
Granular Geomechanics provides a comprehensive exploration of soils as granular materials and the manner in which a soil's engineering properties form grain-scale mechanics. The book focuses on granular composition and packing, grain interactions, discrete granular modeling and continuum constitutive modeling.